PENGARUH PEMBERIAN PUPUK ORGANIK DAN JENIS MULSA ORGANIK TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Merrill) - Ainun Marliah, Nurhayati, dan Dewi Susilawati (Jurnal Floratek, 2011)
A study to determine a right concentration of organic fertilizer Super Nasa and type of organic mulches on growth and yield of soybeans has been conducted. The experiment used a factorial randomized complete block design 4 x 3 with 3 replications. Factors studied were concentrations of organic fertilizer Super Nasa, consisting of 4 levels: 0, 5, 10, 15 g/L of water and types of organic mulches, consisting of three levels: printing newspaper, bagasse, and paddy stalk. Results showed that the concentrations of organic fertilizer Super Nasa exerted highly significant effects on dried grain weight per plot netto and dried seed weight per hectare and exerted a significant effect on plant height 45 day after planting, but exerted no significant effect on other variables. The best growth and yield of soybean were found at a concentration of organic fertilizers Super Nasa 10 g/L of water. Types of organic mulches did not affect all variables observed. However, Soybean yield was apparently better at printing newspaper. There was no significant interaction between concentration of organic fertilizer Super Nasa and types of organic mulches on all growth and yield variables observed.